(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
Some small-scaled Norian-Rhaetian reefs and reef mounds are imbedded within the shales, siltstones and siliciclastic-carbonate deposits of the Nayband Formation in central Iran. These deposits belong to the central Iranian plate as part of the Cimmerian Continent. Most of the biogenic rocks have a biostromal geometry, biohermal constructions are rare. Inozoid, sphinctozoid, and chaetetid sponges are, beside of corals and other reef builders, the most important reef organisms within these bioconstructions. In some reefs a variety of hexactinellid sponges also occur. The following inozoid sponges are described in this paper: Radiofibra norica n. sp., Permocorynella maxima n. sp., ?Sestrostomella robusta, Marawandia iranica, n. gen., n. sp. and Enaulofungia? triassica n. sp. The first four taxa are among the most abundant sponges within the Nayband Formation where it is exposed in several localities in central Iran. Enaulofungia? triassica, however, is not an abundant sponge there. These inozoid sponges have never been reported from the Triassic deposits of this region. Radiofibra, until now known only from the Upper Permian of Djebel Tebaga (Tunisia), is reported here for the first time from Triassic rocks. The stratigraphic as well as the paleogeographic distribution of all the genera are discussed.